The relationship between attitude toward physical activity and weight gain in children and young adolescence - Özer, Ömer; Uyhan, Osman; Devrilmez, Erhan; Orhan, İlkay; Bilgiç, Mert; Uğurlu, Alkan; Tabak, Ekrem Yasin; Yüksel, Oğuzhan; Şentürk, Aydın; Karakullukçu, Ayla; Eler, Nebahat; Özcan, Kürşat; et al. (Frontiers in Pediatrics, 2024)
The purpose of this study was to investigate the association between attitudes toward physical activity and weight gain among children and young adolescents with an additional focus on the impact of gender on these attitudes. Employing a descriptive survey method, data were systematically gathered via purposive sampling from 11 specific cities in Türkiye, ensuring representation from all seven regions. A total of 3138 students, aged between 9 and 14 years, participated in this study, with a distribution of 46% girls and 54% boys. To assess the attitudes of children and young adolescents toward physical activity, the Youth Physical Activity Attitude Scale was utilized. Height and body weight measurements were taken to determine the body mass index of participants. SPSS 26.0 software facilitated the statistical analyses, including Pearson correlation analysis to explore relationships between variables. Multivariate Analysis of Variance was employed to evaluate the impact of age, BMI, and gender on attitudes toward physical activity. Participants classified as normal weight exhibited a more positive attitude towards physical activity compared to their obese and overweight counterparts. Moreover, a significant gender difference emerged, with boys demonstrating significantly higher positive attitudes toward physical activity than girls. However, no significant difference was observed in negative attitudes based on gender. The study also revealed that an escalation in negative attitudes towards physical activity correlated with students being categorized as underweight, overweight, or obese, as opposed to having a normal weight status. Additionally, a statistically significant divergence in both positive and negative attitudes towards physical activity was found based on age. Specifically, the results indicated that students aged 9 and 14 exhibited lower levels of positive attitude when contrasted with their counterparts of different age groups. Conversely, in the domain of negative attitudes, students at the age of 9 scored higher than their peers in other age categories. In conclusion, attitudes towards physical activity can serve as a convenient indicator and guide for assessing the effectiveness of various practices or interventions aimed at promoting physical activity, with recognition of the significant gender difference in positive attitudes among children and young adolescents.